2006
DOI: 10.1016/j.aap.2005.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ontario's extended drinking hours on cross-border cities of Windsor and Detroit

Abstract: Purpose-This study evaluated the cross-border safety impact of extended drinking hours from 1:00 to 2:00 a.m., in licensed establishments in Ontario, Canada.Methods-This study examined patterns in total and alcohol-related casualties in: (1) Windsor, Ontario, Canada compared to Detroit, Michigan, US with a 2:00 a.m. closing time, and (2) Ontario compared to Michigan for overall trends. The criterion outcome indicators were: (1) monthly motor vehicle casualties (major injuries and fatalities) for the city-regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
13
4
Order By: Relevance
“…The findings of the different studies on the impact of extended drinking hours support a complex pattern of outcomes, whereby, in Ontario as a whole, there seems to be no perceived increase in alcohol-related, police-reported MVC casualties (Vingilis et al, 2005) or hospital-reported MVC injuries, although in the high-alcohol-density area of Windsor, Ontario, increases were found in alcohol-related, police-reported MVC casualties (Vingilis et al, 2006), and for Ontario as a whole, increases in non-MVC hospital-reported injuries were found for the period during which the drinking hour was extended. Thus, the change in policy, the limited implementation, and other societal factors such as economic conditions and road safety countermeasures may have mediated the effects of the extended drinking hours on MVC injuries but not on non-MVC injuries, such as falls and assaults, in Ontario.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of the different studies on the impact of extended drinking hours support a complex pattern of outcomes, whereby, in Ontario as a whole, there seems to be no perceived increase in alcohol-related, police-reported MVC casualties (Vingilis et al, 2005) or hospital-reported MVC injuries, although in the high-alcohol-density area of Windsor, Ontario, increases were found in alcohol-related, police-reported MVC casualties (Vingilis et al, 2006), and for Ontario as a whole, increases in non-MVC hospital-reported injuries were found for the period during which the drinking hour was extended. Thus, the change in policy, the limited implementation, and other societal factors such as economic conditions and road safety countermeasures may have mediated the effects of the extended drinking hours on MVC injuries but not on non-MVC injuries, such as falls and assaults, in Ontario.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, it is possible that those who tend to get arrested for drunk driving gravitate toward counties with later business hours. Indeed the finding that adjacent county hours were correlated with first-time DWI arrests suggests that people may drive to nearby counties to drink later and subsequently get arrested near to home [12]. Alternatively, outlet business hours may have been extended due to the same societal attitudes which promote drunk driving.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, past research has demonstrated that longer outlet business hours in one region affect alcohol-involved motor vehicle incidents in adjacent regions [12]. This likely reflects the fact that people often travel to adjacent regions for the purposes of drinking, and then return through both the region where they were drinking and their home region.…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggested that these results could be possibly explained by many licenced establishments non-extending their drinking hours, or may be due to insensitivity of Motor Vehicle Collision (MVC)fatality data to detect changes 10. In a subsequent study, the same authors found increased motor vehicle fatalities in the Windsor region (p=0.035) and a cross-border reduction of motor vehicle collision (MVC) fatalities in a neighbouring area of Detroit, USA (p<0.0001) 27. This increase in motor vehicle fatalities could be explained by the ‘re-patriated’ local drivers, since there was a decrease for local drivers being involved in motor vehicle collisions in the neighbouring region after the extension of the closing hours.…”
Section: Resultsmentioning
confidence: 95%